2010
DOI: 10.1097/tp.0b013e3181caeead
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in Cardiovascular Death After Kidney Transplantation

Abstract: These trends suggest improvements in CVS risk management and outcomes in the kidney transplant population in Australia and New Zealand.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
142
0
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 190 publications
(153 citation statements)
references
References 25 publications
3
142
0
8
Order By: Relevance
“…Compared with the general population, KTRs are at a 3-to 5-fold higher risk (2), with some improvement in recent years (3). Calcification of the arterial wall is a strong cardiovascular risk factor in the general population (4-7), in patients on dialysis (8) and in KTRs (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the general population, KTRs are at a 3-to 5-fold higher risk (2), with some improvement in recent years (3). Calcification of the arterial wall is a strong cardiovascular risk factor in the general population (4-7), in patients on dialysis (8) and in KTRs (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…Although short-and intermediate-term graft survival has improved with the introduction of calcineurin inhibitors (CNIs) in the 1980s, the rate of graft failure beyond 10 years posttransplant has remained unchanged (2). Chronic allograft nephropathy (CAN; also defined as nonspecific interstitial fibrosis and tubular atrophy [IFTA]) and death with functioning graft (DFG) are the two most common causes of late graft loss, with cardiovascular disease (CVD) and cancer demonstrated to be the two most frequent causes of DFG (3,4). In Australia, 40% and 43% of graft loss are attributed to CAN and DFG, respectively (2).…”
Section: Introductionmentioning
confidence: 99%
“…We demonstrated that advanced age, increased SBP, serum osteoprotegerin levels to some extent, but CV disease still remains the leading cause of death in renal transplant recipients (22). Beside the factors mentioned above, why the Rtx patients are more prone to worse CV outcomes and why these anticipated events remain after Rtx are still unclear.…”
Section: Türk Nefroloji Diyaliz Ve Transplantasyon Dergisi Turkish Nementioning
confidence: 99%